2020
DOI: 10.1371/journal.pone.0240113
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of milk production of dairy cows vaccinated with a live double deleted BVDV vaccine and non-vaccinated dairy cows cohabitating in commercial herds endemically infected with BVD virus

Abstract: Daily milk production and reproductive performance of cows vaccinated with a live doubledeleted Bovine Viral Diarrhoea Virus (BVDV) vaccine were compared to those of non-vaccinated cows, cohabitating in endemic BVDV herds. All animals in the treatment group were vaccinated on study day 0 irrespective of lactation or gestation status, while control animals did not receive any treatment. 1463 animals were enrolled in the study from four different farms in three different countries (UK, Italy, France). Endemic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Both clinical mastitis and immune suppression followed by increased feed energy used for immune function and been suggested as plausible modes by which BVDV could affect milk production (Heuer et al, 2007). A recent report indicated that cows vaccinated with MLV produced more milk than non-vaccinates during the first 100 days of lactation (Schmitt-van de Leemput et al, 2020). In the present study, daily milk production was not reduced during P2.…”
supporting
confidence: 38%
“…Both clinical mastitis and immune suppression followed by increased feed energy used for immune function and been suggested as plausible modes by which BVDV could affect milk production (Heuer et al, 2007). A recent report indicated that cows vaccinated with MLV produced more milk than non-vaccinates during the first 100 days of lactation (Schmitt-van de Leemput et al, 2020). In the present study, daily milk production was not reduced during P2.…”
supporting
confidence: 38%